MICRO BUSINESS’ FINANCIAL RECORDING ASSISTANCE AT BANJARAGUNG VILLAGE THROUGH SIMPLE CASH BOOKKEEPING - Kusuma Wardhani Mas’udah; Eka Restu Justitian; Salsabyla Kirana Gani Famulya; Ratna Fransiska Anggraeni; Ratih Mustika Dewi; Andre Zakariya Putra (Pusat Riset dan Inovasi Nasional, 2022)
Micro Business has an important role for the nation's economy, especially to reduce the unemployment rate in Indonesia. The existence of Micro Business in Indonesia is proven to be able to create jobs and absorb labors. Therefore, Micro Business' players must understand good and systematic financial management so that the business can run smoothly and sustainably. For example: to have correct financial records in recording every financial transaction and be able to make financial reports needed to make decisions for the continuity of their business. This research uses descriptive qualitative research methods, which the subjects are five Micro Businesses in Banjaragung Village, Bareng District, Jombang Regency. The object of this research is a financial bookkeeping system that focuses on micro-enterprise cash bookkeeping. The result of the training and mentoring activities in making simple financial bookkeeping is that Micro Businessmen in Banjaragung Village can understand their income and expenses of respective businesses. The personal property must be distinguished from business assets. And at the end, Micro Businessmen can continuously apply simple financial bookkeeping for business activities on a daily basis. This activity can encourage businesses to grow and well developed.